2011
DOI: 10.1089/hum.2011.070
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Advanced Leukemia in Mice with mRNA Engineered T Cells

Abstract: Cytotoxic T lymphocytes (CTLs) modified with chimeric antigen receptors (CARs) for adoptive immunotherapy of hematologic malignancies are effective in preclinical models and are being tested in several clinical trials. Although CTLs bearing stably expressed CARs generated by integrating viral vectors are efficacious and have potential long-term persistence, this mechanism of CAR expression can potentially result in significant toxicity. T cells were electroporated with an optimized in vitro transcribed RNA enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
193
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 195 publications
(201 citation statements)
references
References 54 publications
5
193
0
3
Order By: Relevance
“…Such approaches would include the use of "biodegradable" CART-engineered cells such as T cells electroporated with CAR messenger RNA developed by our group and others, which transiently express the CAR transgenes and thus have a finite and short lifespan; the use of "biodegradable" CAR-engineered T cells modified with messenger RNA; the use of inducible suicide systems to ablate engineered cells when desired; the use of costimulatory molecules less potent than CD137; or the use of T-cell-depleting antibodies such as antithymocyte globulin or alemtuzuzmab. [45][46][47] A subsequent infusion of healthy hematopoietic stem cells may be then needed to reconstitute normal hematopoiesis.…”
Section: Discussionmentioning
confidence: 99%
“…Such approaches would include the use of "biodegradable" CART-engineered cells such as T cells electroporated with CAR messenger RNA developed by our group and others, which transiently express the CAR transgenes and thus have a finite and short lifespan; the use of "biodegradable" CAR-engineered T cells modified with messenger RNA; the use of inducible suicide systems to ablate engineered cells when desired; the use of costimulatory molecules less potent than CD137; or the use of T-cell-depleting antibodies such as antithymocyte globulin or alemtuzuzmab. [45][46][47] A subsequent infusion of healthy hematopoietic stem cells may be then needed to reconstitute normal hematopoiesis.…”
Section: Discussionmentioning
confidence: 99%
“…These could include hematopoietic stem cell transplantation, incorporation of a suicide gene within the CAR construct, or transiently transfecting T cells with the CAR construct. 49,50 Indeed, in preliminary studies we have demonstrated the feasibility of using RNA transfection to express anti-CD33-41BB-ζ CAR on T cells (data not shown).…”
mentioning
confidence: 94%
“…Furthermore, treatment of human ALL cell line-xenografted mice with retrovirus-or lentivirus-transduced CD19 CAR T cells (second generation) resulted in systemic trafficking of T cells to sites of CD19+ disease and in successful eradication of leukemia [Brentjens et al 2007;Milone et al 2009;Barrett et al 2011].…”
Section: Cd19-redirected Car T Cells: Optimal Designmentioning
confidence: 99%